PERAN STAKEHOLDER DALAM MEWUJUDKAN SUSTAINABLE ENVIRONMENTAL DENGAN MENGGALAKKAN SEKOLAH RAMAH LINGKUNGAN DI MA DARUL HUDA PANDEGLANG - Lailatul Idzharo (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
Climate change and environmental degradation have become urgent global issues to be addressed. The negative impacts of human activities on the environment are increasingly being felt, one of which is the accumulation of waste. Green economy is an economic concept related to the distribution, production and consumption of goods and services, which in its application will incur environmental costs. The purpose of the Community Service initiative (PKM) is to increase students' awareness of the importance of preserving the environment by conducting waste management. The PKM team taught MA Darul Huda Pusat Mandalawangi students about the role of school officials in environmentally friendly school management, how to manage waste, and make waste containers from used gallons, which means that the participants were involved in the activities carried out, such as delivering materials and practicing waste management. This community service activity was held at MA Darul Huda Pusat Mandalawangi on May 2, 2024 which was attended by students of MA Darul Huda Pusat Mandalawangi. The environmental management in school life is an activity carried out by educators and students in the form of maintaining hygiene, sorting waste, processing waste, and preserving the environment.